ANALYSIS OF FACTORS THAT INFLUENCE EMPLOYEE PERFORMANCE (Study on Permanent Employees in Operational Section of PT WIMCycle Indonesia - Surabaya) - Prasetya, Arik (FIA UB, 2018)
The purpose of this study was to describe and examine the factors that affect the performance of employees at PT. Wimcycle Indonesia Surabaya. These factors are grouped into 2 (two): the individual dimensions (abilities, work experience, motivation) and the organizational dimensions (leadership, communication, organizational climate), while for the variable employee performance is the result of work shown by employees at a certain time based on performance standards set. The research sample consisted of 90 employees that divided into several divisions. The questionnaire was developed by researchers using 5-point Likert scale. Data analysis techniques using descriptive statistics and multiple linear regression. Multiple linear regression model with six independent variables could explain 54.5% of the variation of the variable employee performance. Partially it can be seen that out of the six independent variables in this study, the capability of employees to have the most influence on employee performance.Â